(untitled) (Zaporizhzhia Historical Review, 2021)
The author contends that in post-war years there were three active pro-Soviet political groups that formed the future model for the development of post-war Poland, namely the Polish Workers Party in Poland, the Union of Polish Patriots and the Central Bureau of Polish Communists in the Soviet Union. the Union of Polish Patriots and the Central Bureau of Polish Communists formally followed the tactics of preserving the multi-party system in the liberal and democratic society. The leaders of the Polish Workers Party were leaning towards Leninís concept of power and were laying the foundation of a dictatorship society.